Analysis of Employee Work Motivation to Increase Work Productivity at PT. Bank Syariah Indonesia KC Sibolga - Rustiana, Devara; Ramadhani, Sri; Syarvina, Wahyu (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research explores key aspects of work motivation that affect employee productivity at PT. Bank Syariah Indonesia KC Sibolga in order to improve employee performance and PT operations. Bank Syariah Indonesia KC Sibolga. The research uses descriptive qualitative methods in observing the natural conditions of employee work productivity at PT. Bank Syariah Indonesia KC Sibolga. comes from interviews, direct observations, and journal articles and other relevant scientific publications. Analyzed by data reduction, data presentation and conclusions. Researchers validated the data using the triangulation method. The results of this research indicate that non-optimality in motivating employees can cause boredom and hinder productivity. To overcome this, companies are advised to adopt proactive steps, such as changes in corporate culture, team building activities, recognition of achievements, and integration of sharia values. Training and development programs are also needed to improve employee skills, while a fair reward system can create a competitive work environment. Effective management strategies and a focus on information technology have had a positive impact on employee productivity, with careful planning, good organization, and the adoption of advanced technology reducing routine workload, increasing operational efficiency, and rewarding technological development. All this contributes to employee satisfaction and improved quality of service to customers.